Mashups and other new or improved collaborative social software tools - Lackie, Robert J; Terrio, Robert D (MultiMedia & Internet@Schools, 2007)
A recent article in MultiMedia & Internet@Schools discussed some practical Web 2.0 tools for librarians and educators to begin using: blogging with Blogger, reading RSS feeds with Bloglines, social bookmarking with del. icio. us, and building wikis with PBwiki.com (Lackie 2006b).